Governança corporativa e a funcionalidade do sistema bancário brasileiro - Rubens Jose Amaral de Brito (2011)
The relationship between the corporate governance and the financial intermediation is a theme little studied by Economic Theory. Although there is a vast literature that relates banking system with economic growth, few attention has been paid, so far, in understanding the role of corporate governance in the process of allocation of resources to finance investment. This thesis is an attempt to fill this gap. There are three main contributions: to present a typology for corporate governance systems, applying it to the Brazilian banking system; to propose an indicator for finance, which represents the allocation of resources, by the banking firms, in a type of financing that allows investors to start the investment process; and analyze the importance of corporate governance system on process of allocation of resources in finance. The typology that characterizes the corporate governance system has three dimensions: the relationship with stakeholders, the capital structure and the corporate control mechanisms. It has been constructed corporate governance index for each one of these dimensions. These indexes are the main explanatory variables used in the analysis. Besides these, the work used control variables that capture situational aspects and specific characteristics of banking firms. Using a database consisting for banking firms with stocks traded on BM&FBovespa between 2005 and 2009, the findings suggested that all three dimensions of corporate governance system are significant in explaining the decision of allocation of resources in finance. Other things equal, the relationship with stakeholders and the capital structure showed positive and significant relation in all estimates performed. The variable of corporate control mechanisms, however, is affected by certain control variables, which may indicate that it is employed as a way to improve business management, when the capital is opened in stock market, which often is done mandatory by the rules imposed by CVM and are not motivated by a process of improvement of productivity.